BEGINNINGS, CONDITIONS AND PERSPECTIVES OF TOURISM IN THE CITY OF SHTIP - Dimitrov, Nikola V; Atanasova, Simona (Journal of process management and new technologies, 2018)
For a scientists is a challenger to explore the beginning and the course of tourism in smaller cities.The emergence of tourism in Shtip is from a recent date. However, through the example of tourism in Shtip, we identify two historical periods: the preturism and the period of tourism.Thus, the first period lasts until the appearance of the first hotel in 1912, and the second from the middle of the twenties of the 20th century.Serious data on the tourism in Shtip are obtained from the end of the 1950's onwards.The analysis is based on primary and secondary data sources. From the analysis we learn that the tourism in Shtip in recent years has been growing with real development perspectives of diverse tourist offer and production.